To find the product of the polynomial expressions \((xy + 1)(x - 3)\), we can use the distributive property (also known as the FOIL method for binomials):
-
Distribute \(xy\) through \((x - 3)\):
- \(xy \cdot x = x^2y\)
- \(xy \cdot (-3) = -3xy\)
-
Distribute \(1\) through \((x - 3)\):
- \(1 \cdot x = x\)
- \(1 \cdot (-3) = -3\)
Now, combine all these results: \[ x^2y - 3xy + x - 3 \]
Thus, the product of the polynomial expressions \((xy + 1)(x - 3)\) is: \[ x^2y - 3xy + x - 3 \]
The correct response is: x²y − 3xy + x − 3